Discernment in 1 Thessalonians - P. Sciberras (Acta Theologica)
This article analyses Paul’s use of ?????????? in 1 Thessalonians 5:21 within the context of verbs for discernment (??????????, ?????????, ?????????? and their cognates). It discusses Paul’s use of these verbs against the background of discernment in the Septuaginta. Paul’s own understanding of discernment is then further investigated in terms of his socio-religious background and other New Testament books. It shows how he links discernment with a concrete situation and how discernment enables the human heart to realise its full potential by purifying it from all obstacles. It then discusses how the present tense of the imperative ?????????? in 1 Thessalonians 5:21 points towards the ongoing nature of discerning God’s will and, finally, how Paul’s eschatological context in 1 Thessalonians implies that discernment also has a future dimension.